2018
DOI: 10.1016/j.jflm.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Documentation and analysis of traumatic injuries in clinical forensic medicine involving structured light three-dimensional surface scanning versus photography

Abstract: Non-contact three-dimensional (3D) surface scanning has been applied in forensic medicine and has been shown to mitigate shortcoming of traditional documentation methods. The aim of this paper is to assess the efficiency of structured light 3D surface scanning in recording traumatic injuries of live cases in clinical forensic medicine. The work was conducted in Medico-Legal Centre in Benghazi, Libya. A structured light 3D surface scanner and ordinary digital camera with close-up lens were used to record the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
1
20
0
1
Order By: Relevance
“…Three-dimensional imaging, virtual environments, and simulations are now becoming commonplace in the reconstruction and documentation of crime scenes, artefacts, and skeletal evidence [9][10][11][12][13][14][15][16]. Ampanozi et al [17] demonstrated that the use of 3D reconstructions and colour-coded CT images were a preferred visual format for district attorneys for understanding radiological findings.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional imaging, virtual environments, and simulations are now becoming commonplace in the reconstruction and documentation of crime scenes, artefacts, and skeletal evidence [9][10][11][12][13][14][15][16]. Ampanozi et al [17] demonstrated that the use of 3D reconstructions and colour-coded CT images were a preferred visual format for district attorneys for understanding radiological findings.…”
Section: Introductionmentioning
confidence: 99%
“…In this research, the mannequins were physically manipulated while the scanner (camera and projector) was tilted and rotated to expose these areas to the light for the optimal working of the camera. The areas were scanned, and the angulation of the scanner during the 3D scanning had no impact on the 3D results . Figure shows the 3D result of the undermined area of the stage‐4 pressure injury (mannequin B).…”
Section: Resultsmentioning
confidence: 99%
“…The Pico scan portable structured light 3D scanner has been applied to reconstruct various traumatic injuries from living victims , and the Artec Eva hand‐held structured light 3D scanner has been used to scan injury tattoos on a volunteer subject . It has been shown that these 3D methods are more useful and address the main shortcomings of digital photography that relate to lighting conditions, angle of acquisition and distance . Additionally, linear 3D wound measurements based on these techniques have been validated in both studies.…”
mentioning
confidence: 99%
“…Recent work (Shamata and Thompson, 2018) has shown that the use of 3D surface scanning can support the work of forensic medical practitioners, partly by allowing for surface detail to be recorded with topographic anatomical detail. This approach was attempted here using a FARO Gage Plus.…”
Section: Methodsmentioning
confidence: 99%